(untitled) (Andamios, Revista de Investigación Social, 2025)
This article aims to demonstrate how historical memory holds an inherent justice within its processes, which could be termed historical justice due to its relationship with identity. This purpose is inspired by the experience of the Association of Relatives of Victims of the Trujillo Massacre (AFAVIT), Colombia. Historical justice is a concept that emerges from the connection between historical memory and identity: the act of reclaiming it in relation to the narrative of the past. This vindication is conceived as a form of justice, based on the equality sought to be restored both in justice and in historical memory, and represents an interpretation of the relationship between the two that transcends transitional justice and criminal justice. The arguments developed are inspired by writings from AFAVIT leaders and testimonies from some of its members, as well as supported by various studies on the topics addressed.